2021
DOI: 10.1038/s42003-021-02109-x
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent neuroimaging and neurostimulation reveals a causal role for dlPFC in coding of task-relevant information

Abstract: Dorsolateral prefrontal cortex (dlPFC) is proposed to drive brain-wide focus by biasing processing in favour of task-relevant information. A longstanding debate concerns whether this is achieved through enhancing processing of relevant information and/or by inhibiting irrelevant information. To address this, we applied transcranial magnetic stimulation (TMS) during fMRI, and tested for causal changes in information coding. Participants attended to one feature, whilst ignoring another feature, of a visual objec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 132 publications
0
16
0
Order By: Relevance
“…While evidence for multivariate control has a long history in attentional tracking (Pylyshyn and Storm, 1988;Vul et al, 2009), including parametric relationships between attentional load and IPS activity (Culham et al, 2001(Culham et al, , 1998Howe et al, 2009;Jovicich et al, 2001;Ritz et al, 2022b), little is known about how the brain coordinates multiple control signals (Ritz et al, 2022a). Future experiments should further elaborate on this frontoparietal control circuit, interrogating how incentives influence different task representations (Etzel et al, 2016;Hall-McMaster et al, 2019;Parro et al, 2018;Peck et al, 2009;Wisniewski et al, 2015), and how neural and behavioral indices of control causally depend on perturbations of neural activity (Jackson et al, 2021). Future experiments should also use temporally-resolved neural recording technologies like (i)EEG or (OP-)MEG to better understand the within-trial dynamics of multivariate control (Ritz and Shenhav, 2021;Weichart et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While evidence for multivariate control has a long history in attentional tracking (Pylyshyn and Storm, 1988;Vul et al, 2009), including parametric relationships between attentional load and IPS activity (Culham et al, 2001(Culham et al, , 1998Howe et al, 2009;Jovicich et al, 2001;Ritz et al, 2022b), little is known about how the brain coordinates multiple control signals (Ritz et al, 2022a). Future experiments should further elaborate on this frontoparietal control circuit, interrogating how incentives influence different task representations (Etzel et al, 2016;Hall-McMaster et al, 2019;Parro et al, 2018;Peck et al, 2009;Wisniewski et al, 2015), and how neural and behavioral indices of control causally depend on perturbations of neural activity (Jackson et al, 2021). Future experiments should also use temporally-resolved neural recording technologies like (i)EEG or (OP-)MEG to better understand the within-trial dynamics of multivariate control (Ritz and Shenhav, 2021;Weichart et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A compelling possibility is that the cognitive control system uses a similar representational format to coordinate multiple control signals within a task as well (Ebitz et al, 2020;Libby and Buschman, 2021;Rust and Cohen, 2022). A large body of work has shown that cognitive control networks encode multiple task parameters (Flesch et al, 2022;Freund et al, 2021;Jackson et al, 2017Jackson et al, , 2021Kayser et al, 2010b;Vermeylen et al, 2020;Woolgar et al, 2011Woolgar et al, , 2015bWoolgar et al, , 2015a, and 'global' measures of cognitive control like overall difficulty or effort (Freund et al, 2021;Kragel et al, 2018;Smith et al, 2019;Vermeylen et al, 2019). However, little is known about whether different control parameters are encoded independently from one another, which would allow the brain to simultaneously coordinate multiple forms of goaldirected task processing.…”
Section: Introductionmentioning
confidence: 99%
“…To do so, we started with the 69 studies reported by Bergmann et al (2021) and then, using equivalent search criteria, looked for additional studies published in 2020 and 2021, which resulted in five additional studies (Cobos Sánchez et al, 2020;Navarro de Lara et al, 2020;Jackson et al, 2021;Rafiei et al, 2021;Scrivener et al, 2021). Second, we excluded two sets of articles: (1) papers that primarily focused on methodological issues and only reported data from a single subject (Bestmann et al, 2003a(Bestmann et al, , 2006Peters et al, 2013;Navarro de Lara et al, 2015;Oh et al, 2019), and (2) papers that did not provide information that allows the determination of whether or not TMS led to an increase in local BOLD activation because relevant analyses were not reported (Ruff et al, 2006(Ruff et al, , 2008Guller et al, 2012;Chen et al, 2013;Hanlon et al, 2016;Fonzo et al, 2017;Cobos Sánchez et al, 2020;Eshel et al, 2020;Hermiller et al, 2020;Navarro de Lara et al, 2020;Jackson et al, 2021;Oathes et al, 2021;Scrivener et al, 2021). Among the remaining studies, two pairs of studies shared the same underlying dataset (Leitão et al, 2013and Shitara et al, 2011 and, therefore, we kept only the ones that explicitly mention results related to the presence or absence of activation at the site of stimulation (Shitara et al, 2011;Leitão et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…S1). Alternatively, recent TMS-fMRI studies targeting the DLPFC have also not detected a BOLD response in the targeted DLPFC location [42,43], suggesting that stimulation of prefrontal cortical tissue may evoke different neurophysiological responses than stimulation of other cortical areas (e.g., motor cortex) that show intensity-dependent BOLD responses [44,45].…”
Section: As Predicted Tms Increased High Cognitive Load Related Deact...mentioning
confidence: 99%